FOXO3a Mediates Homologous Recombination Repair (HRR) via Transcriptional Activation of MRE11, BRCA1, BRIP1, and RAD50 - Gozde Inci; Madhuri Shende Warkad; Beom-Goo Kang; Na-Kyung Lee; Hong-Won Suh; Soon Sung Lim; Jaebong Kim; Sung-Chan Kim; Jae-Yong Lee (Molecules, 2022)
To test whether homologous recombination repair (HRR) depends on FOXO3a, a cellular aging model of human dermal fibroblast (HDF) and tet-on flag-h-FOXO3a transgenic mice were studied. HDF cells transfected with over-expression of wt-h-FOXO3a increased the protein levels of MRE11, BRCA1, BRIP1, and RAD50, while knock-down with siFOXO3a decreased them. The protein levels of MRE11, BRCA1, BRIP1, RAD50, and RAD51 decreased during cellular aging. Chromatin immunoprecipitation (ChIP) assay was performed on FOXO3a binding accessibility to FOXO consensus sites in human MRE11, BRCA1, BRIP1, and RAD50 promoters; the results showed FOXO3a binding decreased during cellular aging. When the tet-on flag-h-FOXO3a mice were administered doxycycline orally, the protein and mRNA levels of flag-h-FOXO3a, MRE11, BRCA1, BRIP1, and RAD50 increased in a doxycycline-dose-dependent manner. In vitro HRR assays were performed by transfection with an HR vector and I-SceI vector. The mRNA levels of the recombined GFP increased after doxycycline treatment in MEF but not in wt-MEF, and increased in young HDF comparing to old HDF, indicating that FOXO3a activates HRR. Overall, these results demonstrate that MRE11, BRCA1, BRIP1, and RAD50 are transcriptional target genes for FOXO3a, and HRR activity is increased via transcriptional activation of MRE11, BRCA1, BRIP1, and RAD50 by FOXO3a.